2006
DOI: 10.1254/jphs.cr0050032
|View full text |Cite
|
Sign up to set email alerts
|

The Sigma1 Protein as a Target for the Non-genomic Effects of Neuro(active)steroids: Molecular, Physiological, and Behavioral Aspects

Abstract: Abstract. Steroids synthesized in the periphery or de novo in the brain, so called 'neurosteroids', exert both genomic and nongenomic actions on neurotransmission systems. Through rapid modulatory effects on neurotransmitter receptors, they influence inhibitory and excitatory neurotransmission. In particular, progesterone derivatives like 3α-hydroxy-5α-pregnan-20-one (allopregnanolone) are positive allosteric modulators of the γ-aminobutyric acid type A (GABA A ) receptor and therefore act as inhibitory steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 186 publications
(198 reference statements)
3
112
0
7
Order By: Relevance
“…Consequently, increases in s 1 receptor expression or affinity may have amplified the effects of BD1047 in the cocaine-exposed but not drug-naïve SCM group, providing a possible explanation for the differential efficacy of BD1047 in reversing behavior induced by the cocaine vs SCM S + . Several endogenous systems have been shown to interact with the s 1 receptor, including peptides of the neuropeptide Y and calcitonin gene-related peptide families and neuroactive steroids that have attracted much interest recently as putative endogenous ligands for the s 1 receptor (for reviews, see Maurice, 2004;Monnet and Maurice, 2006). Specifically, it has been shown that pregnenolone and DHEA act as s 1 receptor agonists, progesterone being the most potent endogenous s 1 receptor antagonist known to date (Maurice, 2004;Maurice et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, increases in s 1 receptor expression or affinity may have amplified the effects of BD1047 in the cocaine-exposed but not drug-naïve SCM group, providing a possible explanation for the differential efficacy of BD1047 in reversing behavior induced by the cocaine vs SCM S + . Several endogenous systems have been shown to interact with the s 1 receptor, including peptides of the neuropeptide Y and calcitonin gene-related peptide families and neuroactive steroids that have attracted much interest recently as putative endogenous ligands for the s 1 receptor (for reviews, see Maurice, 2004;Monnet and Maurice, 2006). Specifically, it has been shown that pregnenolone and DHEA act as s 1 receptor agonists, progesterone being the most potent endogenous s 1 receptor antagonist known to date (Maurice, 2004;Maurice et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous ligand of s 1 receptors has not been fully identified yet. However, several lines of evidence suggest that neuroactive steroids such as dehydroepiandrosterone (DHEA) and progesterone act as potent endogenous s 1 receptor modulators (for review, see Monnet and Maurice, 2006). Behaviorally, s 1 receptors have been implicated in cognitive function, anxiety, depression, and regulation of stress responses (eg Maurice et al, 2001;Urani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, progesterone has been shown to block several receptors that may modulate psychotic-like actions, such as sigma or 5-HT 3 receptors (Monnet and Maurice, 2006;Wetzel et al, 1998). Indeed, the blockade of these receptors has previously been shown to reduce spontaneous activity in rodents and to antagonize AMPHmediated hyperactivity (Costall et al, 1987;Wang et al, 1992).…”
Section: -A-reductase Inhibitors In Models Of Psychosis M Bortolato mentioning
confidence: 99%
“…Increasing or activating s 1 proteins is expected to counteract ER stress response, whereas decreasing or inactivating them would enhance apoptosis (Hayashi and Su, 2007). Modifying s 1 protein activation using selective activators/agonists therefore mediates a unique pharmacological action on Ca 2 + homeostasis and signal transduction pathways, which has proven to allow an effective neuroprotection against several kinds of insults, including excitotoxicity, oxidative stress, and amyloid toxicity (for reviews, see Maurice et al, 2006;Monnet and Maurice, 2006). Indeed, preliminary experiments showed that, in vitro, the selective s 1 activators PRE-084 and MR-22 attenuate the Ab 25-35 -induced expression of the proapoptotic protein Bax and neuronal death in rat cortical cultures (Marrazzo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%